Wall-eyed bilateral internuclear ophthalmoplegia (webino syndrome) and myelopathy in pyoderma gangrenosum - Marco Aurélio Lana; Paulo Roberto R. Moreira; Leonardo B. Neves (Arquivos de Neuro-Psiquiatria)
A 35-year-old female with pyoderma gangrenosum developed paraparesis with a sensory level at L1. Three months later she complained of diplopia and was found to have bilateral internuclear ophthalmoplegia with exotropia and no ocular convergence. The term Webino syndrome has been coined to design this set of neuro-opthalmologic findings. Although it was initially attributed to lesions affecting the medial longitudinal fasciculus and the medial rectus subnuclei of the oculomotor complex in the midbrain the exact location of the lesion is still disputed. In the present case both myelopathy and Webino syndrome were probably due to vascular occlusive disease resulting from central nervous system vasculitis occurring in concomitance to pyoderma gangrenosum.